Pharmacokinetic Study of Four Major Bioactive Components of Liandan Xiaoyan Formula in Ulcerative Colitis and Control Rats Using UPLC-MS/MS - Zhang, Kaihui; Lu, Zenghui; Wang, Qian; Liu, Fangle; Wang, Meiqi; Lin, Chaozhan; Zhu, Chenchen (Frontiers in Pharmacology, 2022)
Liandan Xiaoyan Formula (LXF), a classic Traditional Chinese medicine (TCM) formula, is composed of two Chinese herbal medicines for treating bowel disease under the TCM theory. This study aimed to develop a rapid, stable, sensitive, and reliable method based on ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) to simultaneously determine four major bioactive components of LXF (andrographolide, dehydroandrographolid, 1-methoxicabony-β-carboline, 4-methoxy-5-hydroxy-canthin-6-one) in rat serum and evaluate the pharmacokinetic characteristics of LXF in ulcerative colitis (UC) and control rats. After pretreating by protein precipitation with methanol, separation was performed on a UPLC C18 column using gradient elution with a mobile phase consisting of acetonitrile and 0.1% formic acid at a flowing rate of 0.4 mL/min. Detection was performed on Triple-TOFTM 5600 mass spectrometry set at the positive ionization and multiple reaction monitoring (MRM) mode. The validated method showed good linearity (R2 ≥ 0.9970), the intra- and inter-day accuracy were within ±11.58%, whereas the intra- and inter-day precision were less than 13.79%. This method was validated and applied to compare the pharmacokinetic profiles of the analytes in serum of UC induced by dextran sulphate sodium (DSS) and control rats after oral administration of LXF. The results showed that four major bioactive components of LXF were quickly absorbed after oral administration in both groups, with higher exposure levels in the UC group. This relationship between the active ingredients' pharmacokinetic properties provided essential scientific information for applying LXF in clinical.